Gypseous Soil Improvement by Silicone Oil - Ibrahim, Ali Nasir; Schanz, Tom (Al-Nahrain Journal for Engineering Sciences, 2017)
Gypseous soils are usually stiff when they are dry especially because of the cementation of soil particles by gypsum, but great loss in strength and sudden increase in compressibility occur when these soils are fully or partially saturated. The dissolution of the cementing gypsum causes high softening of soil. The problem becomes more complicated when water flows through the gypseous soil causing leaching and movement of gypsum. This study examines the improvement of gypseous soil properties using the Silicone oil to minimize the effect of moisture on these soils. This study was conducted on artificial gypseous soil (mixture of 30% Silber sand & 70 % Pure Gypsum) treated with silicone oil in different percentages. The reason for use the silicone oil as an additive to study the gypseous soil properties is due to the leakages of oil products from oil refinery in north of Iraq build on gypseous soil, this oil products infiltrate to the foundation soil of the refinery building facilities. _x000D_ The results showed that the Silicone oil is a good material to modify the basic properties of the gypseous soil of collapsibility and shear strength, which are the main problems of this soil and retained the soil by an appropriate amount of the cohesion suitable for carrying the loads from the structure.